Sleep Disturbances Among Caregivers of Home-Isolated and Hospitalized COVID-19 Patients: A Multi-National Cross-Sectional Study - Turabi, Nafisa; Tomar, Shashi Prabha; Anyagwa, Onyekachi E.; Durganaudu, Hanusha; Ishwarya, V; Kivan, Husam; Bassiony, Mahmoud (Wolters Kluwer Medknow Publications, 2023)
Background:Since the coronavirus (COVID-19) pandemic began, several studies were published on the possible prevention and treatment of the disease caused by severe acute respiratory syndrome coronavirus (SARSCoV-2), and its complications. However, one aspect that was overlooked is the impact on the mental health of the caregivers of COVID-19 patients. The current study endeavors to investigate sleep quality disturbances in the caregivers of COVID-19 patients in different countries.Material and Methods:This cross-sectional multi-center study was performed between August 1, 2021, and August 30, 2022, across 11 countries. A total of 2411 responses meeting the inclusion criteria (being a family member or caregiver involved in patient care) were collected. The sleep quality was assessed using the self-reported Pittsburgh Sleep Quality Index (PSQI) 12. Total scores ranged from 0 to 21. A >= 5 indicated poor sleep quality with 89.6% sensitivity and 86.5% specificity.Results:A total of 2411 responses meeting the inclusion criteria showed that mean PSQI scores (P = 0.3604) were higher in caregivers of hospitalized patients than in patients isolated at home. Approximately 62.4% of caregivers reported sleep quality problems while caring for their patients.Conclusion:The results showed that the majority of caregivers of patients with COVID-19 reported disturbances in sleep quality and impaired sleep was more common among caregivers of hospitalized patients, perhaps because hospitalization is associated with a more severe course of the disease. There is a pressing need to take measures to improve the mental health of these caregivers. There should be treatment programs set up to reverse sleep disturbances in this population sufficiently.
Kras, Magdalena/0000-0002-5627-9333; , V Ishwarya/0000-0003-1978-0951
Keywords: Caregivers; COVID-19; Mental Health; Sleep Disturbances; Sleep Quality